Model Project Based Learning (PJBL) dan Hubungannya dengan Pemahaman Siswa dalam Pembelajaran - Inayah, Zahrotul; Abdul Hakim Majid; Muhammad Lutfi Al Fatih; Aly Masyhar (STIKes Ibnu Sina Ajibarang, 2025)
This study discusses the project based learning model and its relationship to students' understanding in their learning. The method used in this study is a literature study by analyzing various relevant literature. The results of the study indicate that Islamic Religious Education learning is still carried out using conventional methods or lectures that are centered on teachers and students only become listeners, making the atmosphere less interesting and causing a lack of student understanding of the material taught by the teacher. By using the project based learning model approach in Islamic Religious Education learning, students become more active in learning, so that they have the opportunity to develop the material they have obtained. This model constructs student understanding through projects that are worked on, problem solving and experience. So that students have the potential to improve their understanding of Islamic Religious Education material